The Challenges of Socio-Economic Accounting. - Mobley, Sybil C. (The Accounting Review, 1970)
Abstract Changes in the economy have prompted changes in the information needs in all areas of accounting. New cause and effect relationships develop and new concepts emerge which must be given accounting expression. The accounting profession is therefore faced with a need for accounting data which must be accommodated. The magnitude of the challenge reveals the magnitude of the opportunity. There is every reason to believe that socio-economic accounting will provide the thrust necessary to tremendously expand the world of accounting. In this connection, there is an old Hindu saying which seems appropriate here, that "There is no door, but only a small window, that leads to a great new world." However, the saying requires a bit of paraphrasing for, actually, in this case, there is no window. Nevertheless, accounttants do have access to, perhaps, a key hole. The light provided by this small key- hole reveals that there are numerous answers to the challenges posed by socio- economic accounting and they all focus on research.